2016
DOI: 10.46745/ilma.jbs.2016.12.01.13
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Safety Health Environment on Employee Retention in Pharmaceutical Industry: Mediating Role of Job Satisfaction and Motivation

Abstract: Purpose: This study analyzes how employee retention is influenced by factors like safety health environment, job satisfaction and motivation. Methodology/Sampling: This research is quantitative in nature, where 250 survey questionnaires have been distributed within the employees of pharmaceutical industry in Pakistan. SPSS and AMOS have been utilized to analyze the direct and mediating effect of variables. Findings: This study confirms that employee retention is a significant outcome of safety health environme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 22 publications
2
8
0
1
Order By: Relevance
“…As a result, positive thoughts trigger their minds, and they decide to stay. Similarly, past literature evinced a positive association between WPS and ER (Fink-Samnick, 2018;Salman et al, 2016). Based on the existing literature, this study argues that WPS could positively influence ER in the health-care sector.…”
Section: Theoretical Underpinningmentioning
confidence: 52%
“…As a result, positive thoughts trigger their minds, and they decide to stay. Similarly, past literature evinced a positive association between WPS and ER (Fink-Samnick, 2018;Salman et al, 2016). Based on the existing literature, this study argues that WPS could positively influence ER in the health-care sector.…”
Section: Theoretical Underpinningmentioning
confidence: 52%
“…Research conducted by [28] ound that link between job satisfaction and employee retention is significant. This is in accordance with the research conducted by [29] with the results that job satisfaction and employee retention have a positive correlation.…”
Section: C) Relationship Between Job Satisfaction and Employee Retentionmentioning
confidence: 99%
“…Based on the explanation above, the hypothesis proposed in this study are: H2 : Leadership sytle (transformational dan toxic leadership) have a positive on job satisfaction Employee job satisfaction will have consequences for employees to keep working at the company and of course in the long term will affect the operational sustainability of the company. [28], [30], and [29] expressed that there is a prominent linkage between job satisfaction and employee retention. The hypothesis proposed in the study are: H3 : Job satisfaction has a positive effect on employee retention Hypothesis 1 declares that job stress and job satisfaction have a negative influence and hypothesis 3 expresses that job satisfaction has a positive effect on employee retention.…”
Section: Research Hypothesismentioning
confidence: 99%
“…Volume 3, Issue 1, January 2021 [156] It has been concluded that job satisfaction has positive relation with employee retention consequently a study of Pakistan (Salman, Mehmood, Aftab, & Mahmood, 2016) was about the impact of safety health environment on employee retention and pharmaceutical industry in which surveys conducted through questionnaire 250 respondents fill the questionnaire and data analysed through SPSS and Amos.…”
Section: Journal Of Entrepreneurship Management and Innovationmentioning
confidence: 99%
“…To accomplish targets and objectives organizations are attempting to do at its best to continue existing. A study of Pakistan (Salman, Mehmood, Aftab, & Mahmood, 2016) was about the impact of safety health environment on employee retention and pharmaceutical industry in which surveys conducted through questionnaire 250 respondents fill the questionnaire and data analysed through SPSS and Amos in which they shows that pharmaceutical industries attempt retention strategies to retain their talented people.…”
Section: Introduction Backgroundmentioning
confidence: 99%